Gratis. A bordo dell'arte. - Bonito Oliva, Achille (Milano : Skira editore Genève - Milano, 2000)
Abramovic, Marina ; Accardi, Carla ; Benin ; Agnetti, Vincenzo ; Airo, Mario ; Albanese, Giovanni ; Amer, Ghada ; Appel, Karel ; Bacon, Francis ; Bagnoli, Marco ; Bajevic, Maja ; Balestrini, Nanni ; Balla, Giacomo ; Barney, Matthew ; Bartolini, Massimo ; Basquiat, Jean-Michel ; Beecroft, Vanessa ; Benvenuto, Carlo ; Beuys, Joseph ; Bianchi, Domenico ; Bleckner, Ross ; Boetti, Alighiero ; Bourgeois, Louise ; Brandizzi, Marco ; Caira, Giulia ; Canevari, Paolo ; Cannavacciuolo, Maurizio ; Cariello, Letizia ; Castellani, Enrico ; Castellano, Luigi ; Cecchini, Loris ; Ceroli, Mario ; Chia, Sandro ; De Chirico, Giorgio ; Cingolani, Marco ; Clemente, Francesco ; Crespo, Maria Cristina ; Cucchi, Enzo ; Della, Mario ; Depero, Fortunato ; Dessi, Gianni ; Dimitrijevic, Braco ; Diodato, Baldo ; Duchamp, Marcel ; Ducrot, Giuseppe ; Dumb Type ; Fabro, Luciano ; Fontana, Lucio ; Förg, Gunther ; Fraterno, Matteo ; Gallo, Giuseppe ; Gherardi, Isabella ; Gligorov, Robert ; Golub, Leon ; Greenaway, Peter ; Haring, Keith ; Hincapié, Maria Teresa ; Hirst, Damien ; Horiki, Eriko ; Horn, Rebecca ; Horn, Roni ; Isgrò, Emilio ; Jakober, Ben ; Kabakov, Ilya ; Kahlo, Frida ; Kcho ; Kelley, Mike ; Kiefer, Anselm ; Kippenberger, Martin ; Kirchhoff, Thorsten ; Kosuth, Joseph ; Kounellis, Jannis ; Kusama Yayoi ; Kusturica, Emir ; Leto, Alfonso ; Levi, Corrado ; LeWitt, Sol ; Linke, Armin ; Lombardi, Mark ; De Maria, Nicola ; Martegani, Amedeo ; Mauri, Fabio ; McQueen, Steve ; Meteric, Mladen ; Merz, Mario ; Mochetti, Maurizio ; Moffatt, Tracey ; Montesano, Gianmarco ; Mori, Mariko ; Morimura, Yasumasa ; Morley, Malcolm ; Moro, Liliana ; Munari, Bruno ; Neshat, Shirin ; Ochieng, David ; Ono, Yoko ; Onyango, Richard ; Orlan ; Oursler, Tony ; Paladino, Mimmo ; Paolini, Giulio ; etc.
Italiaans
boek